2009
DOI: 10.1111/j.1751-7133.2009.00055.x
|View full text |Cite
|
Sign up to set email alerts
|

Time‐Dependent Changes in B‐Type Natriuretic Peptide After Heart Transplantation: Correlation With Allograft Rejection and Function

Abstract: Endomyocardial biopsy is the gold standard to diagnose cardiac allograft rejection, although a noninvasive modality such as brain natriuretic peptide (BNP) is attractive. The authors examined the correlation of BNP levels with rejection patterns and allograft function in cardiac allograft recipients followed up to 8 years. One hundred forty-four consecutive patients underwent endomyocardial biopsy, right heart catheterization, and blood sampling. BNP levels decreased during the first 6 months after transplant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 23 publications
2
16
0
Order By: Relevance
“…However, most of these studies have focused on diagnostic and not prognostic value, and have used only the single measurements concomitant to the rejection episodes in their analyses. 12,[24][25][26][27] These studies have rendered inconsistent results. Few studies have examined prognostic value of repeated measurements of NT-proBNP or BNP for AR.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…However, most of these studies have focused on diagnostic and not prognostic value, and have used only the single measurements concomitant to the rejection episodes in their analyses. 12,[24][25][26][27] These studies have rendered inconsistent results. Few studies have examined prognostic value of repeated measurements of NT-proBNP or BNP for AR.…”
Section: Discussionmentioning
confidence: 89%
“…14,15 Other studies have found that despite the general decline in NT-proBNP levels after HTx, periodic increase in levels may also be present. 12,16,17 It has been suggested that abnormal renal function 12 and high pulmonary capillary wedge pressures 17 may contribute to this increase. On the other hand, a large study of Bader et al 12 suggested that a role for these clinical variables is less likely in the first 6 months after HTx.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…These levels decreased thereafter, reaching a plateau by about 6 months post-transplantation. 16,17 To avoid this confounder in our analysis, we only included patients who underwent endomyocardial biopsies at Ն180 days post-transplant. All BNP measurements in this study were obtained from blood specimens collected at the time of endomyocardial biopsy procedure.…”
Section: Methodsmentioning
confidence: 99%